Sistem Rekomendasi untuk Optimalisasi Pemilihan Petak Makam di TPU menggunakan Metode Simple Additive Weighting Berbasis Web - Alfi Nurfazri; Naldi Nashih Ulwan; Rinto Priambodo (ISB Atma Luhur, 2021)
In life, there is also death, every day the number of people who are born in the world continues to increase followed by the death of a person. The death rate in DKI Jakarta in early 2020 was 3,072 reports and then there was a significant increase in February as many as 5,792 reports. Public Cemetery is an area of land provided for funeral purposes for any person regardless of religion and class. The City Parks and Forests Service of the Provincial Government of the Special Capital Region of Jakarta is a Regional Work Unit in charge of Forestry, Landscaping, and Cemeteries in the DKI Jakarta Regional Work Scope. The amount of time and energy needed in the funeral process for a corpse in DKI Jakarta Province starts from registering the body, selecting the location to the heir to obtain an IPTM from the PTSP. While the burial process must be carried out quickly, especially in certain conditions, such as during the pandemic, where the bodies must be buried immediately and the limited burial ground available. This recommendation system aims to simplify the process of registering bodies, selecting the cemetery, selecting plots, and managing tombs. By using the SAW method in the selection of cemeteries and grave plots, it will optimize burial plots by selecting the best alternative based on predetermined criteria so that it will reduce TPU cases of fullness or unavailability of grave plots.